IMPLEMENTASI PERATURAN DAERAH NOMOR 4 TAHUN 2014 TENTANG PENYELENGGARAAN KEPARIWISATAAN DI KABUPATEN SEMARANG - Galang Graha Perkasa; Sri Suwitri (Journal of Public Policy and Management Review, 2018)
The Goverment District of Semarang make serious efforts to improve the quality of its tourism. In fact, there are found that the service to invest has not facilitated yet. So the implementation based on Regional Regulation of Semarang Regency number 4 of 2014 on tourism organization has not optimal yet either. The goals of this research is to describe the implementation of Regional Regulation about tourism organization and to identify some things that distracts the implementation. The theory that is used in this research is the model of implementatiom by George Edward III, Merilee S. Grindle,Masmanian and Sebatier. This researxh used a qualitative descriptive approach. The data collecting technique is interview, literature review and documentation. Based on the result of this research, some trouble of implementation was found. The trouble found was on the aspect of purpose and objective, founding and checking, along with the administration sanction that has not been fully optimal. It happened because of its coummunication, content of regulation and variable of environment. The writer suggest that there are should be some simplification of requirements to registry in business tourism and fulfillment right, keep on increasing in founding and checking, and be more straight or clear on its sanction. To make any better, it is necessary to enhance the quality and quantity of its communication, and give more attention to the regulation itself especially on its content and variable of environment.